Efeito preventivo do flavonoide quercetina nos sistemas purinérgico e colinérgico de modelo experimental de hiperlipidemia - Braun, Josiane Bizzi Schlemmer (2017)
Hyperlipidemia (HL) is characterized by changes in lipid metabolism, being one of the main metabolic disorders. HL is recognized as a risk factor for the development of atherosclerosis, characterized by the presence of endothelial dysfunction and an inflammatory process. Extracellular nucleotides and nucleosides are important signaling molecules that modulate the actions of lymphocytes and are essential for the initiation and maintenance of inflammatory reactions. Extracellular levels of these nucleotides are physiologically controlled by the action of an enzyme complex formed by enzymes E-NTPDase, E-5'nucleotidase and E-ADA. These enzymes are located on the surface of lymphocytes and play an important role in maintaining homeostasis. The inflammatory process and the immune response are involved in the formation of atherosclerotic lesions. Cytokines are responsible for modulating aspects of vascular inflammation by altering the proliferation, differentiation and vascular function of a variety of cell types in which intercellular communication occurs. Moreover, changes in cholesterol homeostasis also act negatively on the central nervous system. Acetylcholine is one of the main neurotransmitters of the cholinergic system and is hydrolyzed by acetylcholinesterase, an important regulatory enzyme. AChE is very important in controlling the transmission of nerve impulses through synapses and is therefore considered a good indicator of cholinergic activity. Changes in AChE activity have been associated with memory and learning deficits. In view of this, the interest in disease prevention through food is increasing. Quercetin, present in apples, onions, broccoli, among others, has been studied for presenting antioxidant, anti-inflammatory and neuroprotective actions. Thus, the objective of this study was to evaluate whether the preventive treatment of quercetin is able to prevent the changes caused by HL in the purinergic and cholinergic systems. Male Wistar rats were used and divided into ten groups (n=7), five of them without induction of HL and five with induction. Groups were pretreated with quercetin at doses of 5, 25 and 50 mg / kg for 30 days. After 30 days, P407 (500 mg / kg) was administrated intraperitoneally for induction of HL. Simvastatin (0.04 mg / kg) was also administered after induction as a positive control. The results showed that the preventive treatment with quercetin could reduce the elevated lipid levels induced by HL (P˂0.05). It was also observed in the object recognition test, that there was a significant decrease in the memory of hyperlipidemic rats (P˂0.001), and this alteration was smoothed with the prevention of the preventive treatment of quercetin (P˂0.05). The HL also decreased acetylcholinesterase activity in 52.6% in the hippocampus of hyperlipidemic rats. An increase in E-NTPDase activity of 72% in the ATP hydrolysis) and 98.7% in the ADP hydrolysis the 78% in the E-ADA activity in lymphocytes of hyperlipidemic rats was also demonstrated and pretreatment with quercetin avoided this increase (P˂0.01). Levels of IFN-γ and IL-4 were observed in hiperlipidemic rats (P˂0.01), and that these levels were decreased with quercetin pretreatment (P˂0.05), demonstrating its anti-inflammatory effect. Thus, we conclude that the preventive treatment of quercetin possibly inhibits the inflammatory pathways, reducing the levels of proinflammatory cytokines, modulating the purinergic system and also reversing the changes caused in the HL-induced cholinergic system.